2003
DOI: 10.1016/s0008-6363(03)00458-9
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of the common amino acid 897 polymorphism of the cardiac potassium channel KCNH2 (HERG)

Abstract: The K897T variation has an effect on channel function and clinical phenotype. Our data warrant further investigations into the significance of this polymorphism in drug-induced and inherited LQTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 41 publications
3
65
1
Order By: Relevance
“…When expressed in human embryonic kidney-293 cells, Lys897Thr channels have reduced current density caused by reduced channel expression (34). When patients with the KCNH2 Lys897Thr polymorphism underwent stress testing, their QTc intervals were longer than those of controls (34). Similar observations were made in a study of Finnish women with the KCNH2 Lys897Thr polymorphism (35).…”
Section: Predictors Of Tdp and An Underlying Genetic Mutation Or Polsupporting
confidence: 55%
See 1 more Smart Citation
“…When expressed in human embryonic kidney-293 cells, Lys897Thr channels have reduced current density caused by reduced channel expression (34). When patients with the KCNH2 Lys897Thr polymorphism underwent stress testing, their QTc intervals were longer than those of controls (34). Similar observations were made in a study of Finnish women with the KCNH2 Lys897Thr polymorphism (35).…”
Section: Predictors Of Tdp and An Underlying Genetic Mutation Or Polsupporting
confidence: 55%
“…The KCNH2 Lys897Thr polymorphism in patient 4 has a population frequency of 6% to 30% (33). When expressed in human embryonic kidney-293 cells, Lys897Thr channels have reduced current density caused by reduced channel expression (34). When patients with the KCNH2 Lys897Thr polymorphism underwent stress testing, their QTc intervals were longer than those of controls (34).…”
Section: Predictors Of Tdp and An Underlying Genetic Mutation Or Polmentioning
confidence: 99%
“…Whole-cell patch-clamp recordings were performed using an EPC-9 amplifier and Pulse/Pulsefit software (Heka, Lambrecht, Germany) as described previously (Paavonen et al, 2003). The electrodes had resistances of 2-4 M⍀ when filled with 150 mM KCl, 2 mM MgCl 2 , 5 mM BAPTA, 5 mM Mg 2 ATP 3 and 10 mM HEPES, pH 7.2.…”
Section: Patch-clamp Recordingmentioning
confidence: 99%
“…The distinct properties of iPSC-CMs derived from the proband compared with those derived from the parents reinforce the utility of these cells in detecting patient-specific channel defects and hence improve potential approaches to manage dysfunctional channel activity. Studies in the iPSC-CMs eliminated a role of the common K897T polymorphism in the response of the patient to anti-arrhythmic drug therapies, a particularly important finding because heterologous expression studies have reported differing effects of this variant on channel activity (Bezzina et al, 2003;Paavonen et al, 2003;Anson et al, 2004;Crotti et al, 2005;Rhodes et al, 2008;Sinner et al, 2008). impact of adding a second Na + channel blocker, flecainide, two clinical options frequently used empirically to treat LQTS-3.…”
Section: Discussionmentioning
confidence: 99%
“…Heterologous expression of mutant Na + channels in mammalian (HEK293) cells identified a severe defect in inactivation and illustrated the utility of Na + channel blockers to correct the mutation-induced channel dysfunction (Bankston et al, 2007b). The contribution of the KCNH2 polymorphism to the disease phenotype and pro-and anti-arrhythmic drug effects was unknown despite studies suggesting a causal link between this polymorphism and arrhythmia (Bezzina et al, 2003;Paavonen et al, 2003;Anson et al, 2004;Crotti et al, 2005;Rhodes et al, 2008;Sinner et al, 2008). At the start of the present study, the patient was 4 yr old and was maintained on 24 mg/kg/d mexiletine stem cells (hESCs) derived using the same procedures ( Fig.…”
Section: Na + Channel Activity In Ipsc-cmsmentioning
confidence: 99%